Cotton’s Reactions to Irrigation Management Strategies Applied by Various Irrigation Technologies in Southwest Kansas - Farzam Moghbel; Jonathan Aguilar; Forough Fazel (Kansas Agricultural Experiment Station Research Reports, 2024)
Investigating effective methods in agricultural water management could be a potential solution to address the water scarcity issue and its consequences in the economy of semi-arid regions. A study was conducted in 2023 to identify the benefits of different irrigation technologies and irrigation water management strategies for cotton production in western Kansas. Effects of two configurations of the new mobile drip irrigation (MDI) system (1 gal/h and 2 gal/h) on cotton yield and yield components were compared with a LEPA bubbler and a LESA sprayer to apply 7-day and 14-day irrigation interval strategies. This study so far has revealed the superiority of the combination of either a LESA sprayer or MDI-1 gal/h irrigation with 14-day irrigation intervals in achieving the highest cotton yield in the region.
Keywords: cotton; irrigation; LEPA; LESA; lint yield; MDI